Differential Polarization Imaging of Plant Cells. Mapping the Anisotropy of Cell Walls and Chloroplasts - Radosavljević, Jasna Simonović; Mitrović, Aleksandra Lj; Radotić, Ksenija; Zimányi, László; Garab, Győző; Steinbach, Gábor (International journal of molecular sciences, 2021)
Modern light microscopy imaging techniques have substantially advanced our knowledge about the ultrastructure of plant cells and their organelles. Laser-scanning microscopy and digital light microscopy imaging techniques, in general-in addition to their high sensitivity, fast data acquisition, and great versatility of 2D-4D image analyses-also opened the technical possibilities to combine microscopy imaging with spectroscopic measurements. In this review, we focus our attention on differential polarization (DP) imaging techniques and on their applications on plant cell walls and chloroplasts, and show how these techniques provided unique and quantitative information on the anisotropic molecular organization of plant cell constituents: (i) We briefly describe how laser-scanning microscopes (LSMs) and the enhanced-resolution Re-scan Confocal Microscope (RCM of Confocal.nl Ltd. Amsterdam, Netherlands) can be equipped with DP attachments-making them capable of measuring different polarization spectroscopy parameters, parallel with the 'conventional' intensity imaging. (ii) We show examples of different faces of the strong anisotropic molecular organization of chloroplast thylakoid membranes. (iii) We illustrate the use of DP imaging of cell walls from a variety of wood samples and demonstrate the use of quantitative analysis. (iv) Finally, we outline the perspectives of further technical developments of micro-spectropolarimetry imaging and its use in plant cell studies.
Keywords: Thylakoids; Anisotropy; Plant Cells; chloroplasty; Microscopy, Confocal; konfokální mikroskopie; polarizační mikroskopie; rostlinné buňky; Microscopy, Polarization; Chloroplasts; tylakoidy; anizotropie; Cell Wall; buněčná stěna